Academia and Higher Learning in Popular Culture - Harmes, Marcus K.; Scully, Richard (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This edited volume focuses on the cultural production of knowledge in the academy as mediated or presented through film and television. This focus invites scrutiny of how the academy itself is viewed in popular culture from The Chair to Terry Pratchett's 'Unseen University' and Doctor Who's Time Lord Academy among others. Spanning a number of genres and key film and television series, the volume is also inherently interdisciplinary with perspectives from History, Cultural Studies, Gender Studies, STEM, and more. This collection brings together leading experts in different disciplines and from different national backgrounds. It emphasises that even at a point of mass, global participation in higher education, the academy is still largely mediated by popular culture and understood through the tropes perpetuated via a multimedia landscape. Dr Richard Scully, BA (Hons), PhD (Monash), FRHistS is Associate Professor in Modern History at the University of New England, Australia. His research focuses on the history of cartoons, caricature, and graphic satire. He has co-edited four collections of essays, including two volumes on Australia's migrant and minority press for Palgrave Macmillan. Professor Marcus Harmes is Associate Director Research at the University of Southern Queensland College, Australia, and teaches legal history in the law degree. He has published extensively in the fields of religious and political history, with a particular emphasis on British religious history and constitutional history.
1. Unseen Universities and Seen Academics - An Introduction: Marcus Harmes and Richard Scully -- 2 Absurdism and Entanglement as an Academic Parallel in Terry Pratchett's "Unseen University" : Victoria Hawco -- 3 A Well-Rounded Dick? Academia in 3rd Rock from the Sun: Melissa Beattie -- 4 "I'm a doctor of many things": Tracking the Doctor's Relationship to Traditional Pedagogic Models of Knowledge Creation across Doctor Who: Catriona Mills -- 5 "Do what you like with him": Sherlock Homes' academic training and how it changed over time: Jochem Kotthaus -- 6 Women in the Ivory Tower: Historical Memory and the Heroic Educator in Mona Lisa Smile (2003): Ana Stevenson -- 7 Gods and Monsters in the Ruined University: Filmic Teachers and their Moral Pedagogies from The Faculty to Higher Learning: Susan Hopkins -- 8 A Different Sort of Monster: Science Fiction Casts a Spotlight on the Problematic Power Dynamics of Graduate Programs: Kristine Larsen -- 9 Dystopian Higher Education: A Neoliberal Legacy: Stacy W. Maddern -- 10 Dark Comedies/Dark Universities: Negotiating the Neoliberal Institution in British Satirical Comedies The History Man (1981), A Very Peculiar Practice (1986-1988) and Campus (2011) Bethan Michael-Fox and Kay Calver -- 11 A Doctor Who Academy for Dystopian Times: Robin Redmon Wright -- 12 Conclusions: Marcus Harmes and Richard Scully .
Keywords: Motion pictures; Television broadcasting; Education, Higher; Film and Television Studies; Higher Education